Inclusive Education in Regular Classes from the Perspective of Media Support for Students with Special Needs: Kosovo Case - Osmankaq, Salihe Gajtani; Maloku, Flamur (Journal of Ecohumanism, 2024)
Schools and media continually evolve and impact each other and society in various ways. This study investigates how media contributes to integrating students with special needs into regular pre-university classes and influences the changes in inclusive classroom teaching. Notably, there is a need for a more comprehensive exploration of the relationship between media and inclusive education in Kosovo. Our study investigates the perspectives of teachers instructing in inclusive classrooms (i), parents of students with special needs (ii), and parents of other children (iii). We explore their views on adapting teaching methods in inclusive classrooms and the community’s approach toward children with special needs, whose cases have been highlighted in the media. Our research employs a mixed-methods approach, combining analysis, interviews, and surveys from random samples to gather information from key stakeholders in the field. The study reveals that media significantly impacts everyone’s lives, including children with special needs, their families, and educators. Furthermore, it confirms that media information influences student behavior and the school community, particularly concerning inclusion in education and teaching practices. As a result, our findings recommend that schools and media prioritize identifying elements that either facilitate or hinder inclusion in education and teaching practices in inclusive classrooms. Additionally, efforts should focus on eliminating barriers.